Applications of Algebra to Communications, Control, and Signal Processing - Boston, Nigel; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
None
Introduction -- Algebraic Tools -- Traditional Applications -- Recent Applications to Communications -- Emerging Applications to Signal Processing -- Glossary.
Keywords: Engineering; Data structures (Computer science).; Engineering; Signal, Image and Speech Processing; Data Structures, Cryptology and Information Theory